Calculation of Spectral Optical Constants Using Combined Ellipsometric and Reflectance Methods for Smooth and Rough Bulk Samples. Issue 12 (December 2021) - Fortin, Gilles
Spectra of the optical constants n and k of a substance are often deduced from spectroscopic measurements, performed on a thick and homogeneous sample, and from a model used to simulate these measurements. Spectra obtained for n and k using the ellipsometric method generally produce polarized reflectance simulations in strong agreement with the experimental measurements, but they sometimes introduce significant discrepancies over limited spectral ranges, whereas spectra of n and k obtained with the single-angle reflectance method require a perfectly smooth sample surface to be viable. This paper presents an alternative method to calculate n and k . The method exploits both ellipsometric measurements and s -polarized specular reflectance measurements, and compensates for potential surface scattering effects with the introduction of a specularity factor. It is applicable to bulk samples having either a smooth or a rough surface. It provides spectral optical constants that are consistent with s -polarized reflectance measurements. Demonstrations are performed in the infrared region using a glass slide (smooth surface) and a pellet of compressed ammonium sulfate powder (rough surface). Graphical Abstract